Legal professional restrictions of medical professionals under the legislation of Ukraine: problems and prospects - O. H. Aleksіeіev; M. A. Anishchenko (Zaporozhye State Medical University, 2019)
The aim: to conduct a system analysis of the complex of legislative restrictions in the professional activities of medical professionals from the standpoint of medical law, define the notion of "legal professional restrictions of medical workers", identify problems of legal regulation of these legal relations and outline the ways to resolve them. Materials and methods. The research material is a modern regulatory framework. The methods of information retrieval, analysis, systematization and generalization were carried out. Results. In accordance with the innovations of Article 781of the Fundamentals, from August 1, 2012, medical and pharmaceutical professionals began to be subject to legal restrictions on their professional activities. Simultaneously with the addition of the Fundamentals of the Legislation of Ukraine on Health Protection in Article 781 of the Law of Ukraine, the Code of Ukraine on Administrative Offenses underwent corresponding changes. The introduction of restrictions is quite natural. Having entered into force, these provisions should increase the social responsibility of all participants in a legal relationship, and their main goal is to establish obstacles to possible abuse, create conditions for the independence of professional activity, and guarantee the patient's right to qualified medical care. Conclusions. Legal professional restrictions of medical professionals represent the limitation of professional rights and duties of medical professionals, established by law in order to ensure public interests, prevent offenses, protect the rights and legitimate interests of medical professionals themselves.